2017 25th European Signal Processing Conference (EUSIPCO) 2017
DOI: 10.23919/eusipco.2017.8081355
|View full text |Cite
|
Sign up to set email alerts
|

An optimized embedded target detection system using acoustic and seismic sensors

Abstract: Abstract-Detection of targets using low power embedded devices has important applications in border security and surveillance. In this paper, we build on recent algorithmic advances in sensor fusion, and present the design and implementation of a novel, multi-mode embedded signal processing system for detection of people and vehicles using acoustic and seismic sensors. Here, by "multi-mode", we mean that the system has available a complementary set of configurations that are optimized for different trade-offs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Details about this sensor setup and experiments can be found in [17]. This dataset has been previously used for target detection in [18,19], where the authors focus on detection/classification using seismic and acoustic sensors only. Some data samples from the dataset can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Details about this sensor setup and experiments can be found in [17]. This dataset has been previously used for target detection in [18,19], where the authors focus on detection/classification using seismic and acoustic sensors only. Some data samples from the dataset can be seen in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For details on the algorithms and applications associated with this classification system, we refer the reader to [25,26]. The case study in this paper goes beyond the simulation and prototyping experiments reported in [25,26] in its use of DSGs and DIF-DSG as central parts of the design and implementation process.…”
Section: Case Study: Real-time Classification Systemmentioning
confidence: 99%
“…For details on the algorithms and applications associated with this classification system, we refer the reader to [25,26]. The case study in this paper goes beyond the simulation and prototyping experiments reported in [25,26] in its use of DSGs and DIF-DSG as central parts of the design and implementation process. The experiments described in [25,26] are carried using hand-implemented dataflow graphs that do not employ DSG modeling nor the DIF-DSG software synthesis tool.…”
Section: Case Study: Real-time Classification Systemmentioning
confidence: 99%
See 2 more Smart Citations